A Clinical Study to Evaluate the Efficacy of Kasisadi Vaginal Pessary and Udumbaradi Tail Pichu in Management of Shweta Pradar (Abnormal Vaginal Discharge): A Double Arm Random Control Study (AYUSHDHARA, 2023)
Shwetapradara, a symptom of many gynaecologic disorders, develop due to vitiation of Kapha predominant Doshas. Laghutriya described Shwetapradar. In Charak Samhita management of Shwetpradar is described under the description of Pandurasrigdara. Chakrapani has explained Pandura-Asrigdara as Shwetapradar in his commentary. Objectives: To draw Ayurvedic management to the disease with effective cure and no or minimal side effects, that can be easily administered and accepted by the patient. Materials & Methods: After obtaining Ethics Committee approval and informed consent, 210 patients were randomized into two groups. In one group, Kasisadi vaginal pessary in the night followed by Udumbaradi Taila Pichu for 2 hours in the morning was given while in another a vaginal pessary (clotrimazole+ tinidazole+ clindamycin) was given for 7 days. From baseline to 7th day on the bases of assessment criteria per-speculum examination was done. A comparison of categorical variables was done using an appropriate statistical test. Results: Uduambaradi Taila and Kasisadi vaginal pessary exhibited potentially comparable effects to the conventional treatment but the recurrence rate was found more in conventional treatment. Conclusion: Uduambaradi Taila pichu and Kasisadi vaginal pessary combination is an effective, side effects-free, patient-compliant herbal alternative for the management of abnormal vaginal discharge.